2022
DOI: 10.1038/s41598-022-09139-3
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines and sarcopenia in Iranian adults-results from SARIR study

Abstract: Some studies suggested the effects of inflammatory cytokines in reducing muscle mass and muscle strength and, performance. This study aimed to compare pro-inflammatory cytokines in sarcopenic and non-sarcopenic subjects. 120 men and women were selected out from the cross-sectional study ‘sarcopenia and its determinants among Iranian elders’ (SARIR). Sarcopenia was defined based on the first ‘European Working Group on sarcopenia in older people’ (EWGSOP1) guidelines. A fasting blood sample was taken from each p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…Cognitive impairment may result in reduced physical activity [ 33 , 34 , 35 ], leading to loss of muscle mass. Additionally, several causes of the relationship between a decline in cognitive function and muscle strength and mass have been reported such as inflammation [ 36 , 37 , 38 ], oxidative stress [ 39 , 40 , 41 ], and myokines [ 42 ]. Another explanation is that neuronal degeneration causes a lack of cognitive capacity [ 43 ], and it may also physically decrease muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment may result in reduced physical activity [ 33 , 34 , 35 ], leading to loss of muscle mass. Additionally, several causes of the relationship between a decline in cognitive function and muscle strength and mass have been reported such as inflammation [ 36 , 37 , 38 ], oxidative stress [ 39 , 40 , 41 ], and myokines [ 42 ]. Another explanation is that neuronal degeneration causes a lack of cognitive capacity [ 43 ], and it may also physically decrease muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Bano et al [ 8 ] reported that participants with sarcopenia had significantly higher levels of CRP than the controls, while the levels of TNF-α and IL-6 were insignificantly different. Moreover, Asoudeh et al [ 18 ] found that the levels of CRP, IL-6, and TNF-α were not significantly different between participants with and without low muscle masses as well as those with and without abnormal gait speed tests. However, circulating CRP was elevated among those with a low HGS.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study observed an association between sarcopenia with CRP, ESR, and adiponectin [ 21 ]. By contrast, Asoudeh and her colleagues reported no correlations between IL-6, TNF-α, and CRP with sarcopenia [ 18 ]. Furthermore, Dupont et al [ 22 ] reported that baseline levels of inflammatory markers such as CRP, white blood cell count, and albumin did not predict sarcopenia in elderly men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ιt has been reported that high levels of CRP can lead to a decrease in the size of muscle cells and downregulate protein kinase B (Akt), which is theoretically related to dysregulation of muscle cells [ 36 , 63 ]. Several studies have shown that increasing levels of inflammatory markers, including CRP, in older adults are associated with increased muscle loss and sarcopenia [ 37 ]. Also, high levels of CRP have been reported to be inversely correlated to muscle strength [ 36 , 38 ].…”
Section: Biomarkers With Increased Concentration In Sarcopeniamentioning
confidence: 99%